2001
DOI: 10.1071/ar00107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rumen fluid from South African game species and from sheep to digest tanniniferous browse

Abstract: The hypothesis that South African game animals that use browse containing condensed tannins (CT) could have rumen microbial populations better able to ferment tanniniferous forages was explored. Rumen fluid (RF) from a range of browsing ruminants was used to ferment tanniniferous forages in vitro and the results were compared with the values obtained with rumen fluid from sheep. Leaves of the shrub legumes Leucaena leucocephala, L. pallida, L. trichandra, Calliandra calothyrsus,Gliricidia sepium, and Acacia bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In agreement with the results of Jones et al. (), the present study supports the use of domesticated ruminants as model animals when assessing the digestibility of food consumed by browsing game species. The significant interaction effects on the in vitro fermentation parameters in the present study rather arose due to the incubated samples of the white water lily root, which suggested an existence of a differently dietary adapted ruminal digestion in moose versus dairy cows as previously proposed by Gordon, PĂ©rez‐BarberĂŹa, and Cuartas ().…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the results of Jones et al. (), the present study supports the use of domesticated ruminants as model animals when assessing the digestibility of food consumed by browsing game species. The significant interaction effects on the in vitro fermentation parameters in the present study rather arose due to the incubated samples of the white water lily root, which suggested an existence of a differently dietary adapted ruminal digestion in moose versus dairy cows as previously proposed by Gordon, PĂ©rez‐BarberĂŹa, and Cuartas ().…”
Section: Discussionsupporting
confidence: 93%
“…For example, in a small study Hobson et al (1975) found that the rumen microflora from red deer (Cervus elaphus) fed on a grass diet had a higher fermentation rate on grass hay substrate than on a heather (Calluna vulgaris, a dwarf shrub) substrate. On the other hand, Jones et al (2001) suggested that the rumen microflora of African species of ruminants which browse would be more efficient at digesting browse material than would that of hay-fed sheep, yet no such evidence was found in their study to support this hypothesis. Where interspecific differences in microbial activity have been found, these seem to be associated with differences between species in the diet consumed rather than animal species-specific adaptations (Van Gylswyk and Giesecke 1973;Giesecke and Van Gylswyk 1975;Hoppe et al 1977aHoppe et al , 1977bKennedy et al 1987;Odenyo et al 1999).…”
Section: Introductionmentioning
confidence: 80%
“…Theoretically, herbivores consuming large amounts of tanniniferous forage should possess adaptations to counter any negative effects. Jones et al (2001), however, did not find in vitro evidence for the hypothesis that ruminal microflora of browsing ungulates were better equipped to handle tanniniferous forages than those of grazing ungulates and opined, in keeping with Robbins et al (1991) and Shimada (2006), that binding of ingested tannins with proline-rich saliva may differentiate species that can consume diets high in tannins without ill effects. Of note, salivary proteins of mule deer reduced FN losses per unit of tannin ingested (Robbins et al 1991).…”
Section: Study Focusmentioning
confidence: 91%